Artificial Z-Scheme Constructed with a Supramolecular Metal Complex and Semiconductor for the Photocatalytic Reduction of CO(2) - Sekizawa, Keita (American Chemical Society, 2013)
[Image: see text] A hybrid for the visible-light-driven photocatalytic reduction of CO(2) using methanol as a reducing agent was developed by combining two different types of photocatalysts: a Ru(II) dinuclear complex (RuBLRu′) used for CO(2) reduction is adsorbed onto Ag-loaded TaON (Ag/TaON) for methanol oxidation. Isotope experiments clearly showed that this hybrid photocatalyst mainly produced HCOOH (TN = 41 for 9 h irradiation) from CO(2) and HCHO from methanol. Therefore, it converted light energy into chemical energy (ΔG° = +83.0 kJ/mol). Photocatalytic reaction proceeds by the stepwise excitation of Ag/TaON and the Ru dinuclear complex on Ag/TaON, similar to the photosynthesis Z-scheme.